2022
DOI: 10.1177/21676968211066156
|View full text |Cite
|
Sign up to set email alerts
|

“I Can be Unapologetically Who I Am”: A Study of Friendship Among Black Undergraduate Women at PWIs

Abstract: The current study explores Black undergraduate women’s friendships using in-depth interview data from 47 women (18–24 years) attending predominantly white institutions (PWIs) in the United States. Drawing on consensual qualitative research methods, we considered the nature and importance of Black female friendships among Black undergraduate women. We identified the following themes: (a) friendship as a tool to mitigate bias and discrimination; (b) affinity groups as a gateway to friendship; and (c) friendship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…Tiana benefitted from living closely with other African American women in her residence hall, and she noted that she did not feel like she belonged elsewhere on campus. Her excerpt also indicated that she felt a strong cultural connection to other Black women (i.e., borrowing headscarves), highlighting that these friendships were not just in response to racial isolation on campus (Leath et al, 2022). Many participants also described the importance of Black student organizations on campus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tiana benefitted from living closely with other African American women in her residence hall, and she noted that she did not feel like she belonged elsewhere on campus. Her excerpt also indicated that she felt a strong cultural connection to other Black women (i.e., borrowing headscarves), highlighting that these friendships were not just in response to racial isolation on campus (Leath et al, 2022). Many participants also described the importance of Black student organizations on campus.…”
Section: Resultsmentioning
confidence: 99%
“…We intentionally choose to employ the latter to accentuate the metaphor of “home and family” in how Black students create homeplaces as sites of comfort, healing, love, and resistance against White supremacy. Both concepts highlight Black students’ developing awareness of social structures, but hooks’ notion of homeplace encourages us to expand our understandings of college students’ relationships to include the strong, interdependent community and fictive familial relationships that some Black students build on campus (Leath et al, 2022). We suggest that in creating homeplaces, Black students experience a deepened sense of “mattering”—feeling accepted, respected, and valued by other Black students on campus.…”
Section: Literature and Theory: Blackness Intersectionality Identity ...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a racialized space, campus was not experienced in the same way by all students. Rather than students of color wishing to segregate themselves, they are often seeking (and receiving) support from those with common experiences, which they often find in same-race friends (e.g., Gilkes Borr, 2019;Leath et al, 2022aLeath et al, , 2022bMartínez Alemán, 2000;McCabe, 2009McCabe, , 2015Nenga et al, 2015;Villalpando, 2003). Some students of color, moreover, pursue racially homophilous friendships while others prefer racially diverse friendships (Antonio, 2004b;Gilkes Borr, 2019;McCabe, 2015).…”
Section: Homophilymentioning
confidence: 99%
“…For example, research into the process of how students form homophilous ties finds that Black students strategically build same-race friendships through regularly coming into contact with other Black students in the African American culture-themed residence hall and in Black clubs and activities, such as the Black Student Union (Gilkes Borr, 2019). Many other qualitative studies provide examples of students meeting same-race friends in racial-or ethnic-based clubs, organizations, and activities (e.g., Antonio, 2004b;Leath et al, 2022a;McCabe, 2016;Nenga et al, 2015;Reyes, 2018). Importantly, students also make interracial friendships in student organizations, a finding documented in both quantitative (e.g., Park & Kim, 2013) and qualitative work (e.g., McCabe, 2011).…”
Section: Mccabementioning
confidence: 99%